2003
DOI: 10.3928/1542-8877-20031101-15
|View full text |Cite
|
Sign up to set email alerts
|

Non-Mydriatic Panoramic Fundus Imaging Using a Non-Contact Scanning Laser-Based System

Abstract: * BACKGROUND AND OBJECTIVE: A non contact scanning laser-based retinal imaging system produces a 200° wide-field panoramic image of the fundus through the novel use of a large elliptical mirror. The authors investigated whether accurate diagnoses could be made from these images alone. * PATIENTS AND METHODS: Images were obtained from both eyes of arbitrarily selected patients and were retrospectively reviewed by retinal specialists. Each physician made a diagnosis, suggested the follow-up interval, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(6 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…When seven standard field (SSF) imaging became the gold standard for DR management, it represented a compromise between the excessive time needed to capture up to 30 fields required to document 100% of the retina and getting a "wide enough" view in a more reasonable timeframe. The use of UWF imaging in DR management has grown since research validated that it is at least as sensitive and specific as the Early Treatment Diabetic Retinopathy Study (ETDRS) SSF montages, as nonmydriatic UWF imaging have been reported to have a high sensitivity (84-94%) and specificity (90-100%) for the screening of DR. [18][19][20][21]…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…When seven standard field (SSF) imaging became the gold standard for DR management, it represented a compromise between the excessive time needed to capture up to 30 fields required to document 100% of the retina and getting a "wide enough" view in a more reasonable timeframe. The use of UWF imaging in DR management has grown since research validated that it is at least as sensitive and specific as the Early Treatment Diabetic Retinopathy Study (ETDRS) SSF montages, as nonmydriatic UWF imaging have been reported to have a high sensitivity (84-94%) and specificity (90-100%) for the screening of DR. [18][19][20][21]…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…Subsequently, they designed a non‐contact camera featuring a 90° wide‐angle lens, enhancing contrast by mitigating light reflections from corneal and lenticular surfaces in retinal images [45]. With the continuous progression of technology, Friberg et al [46] introduced a non‐contact scanning retinal imaging system based on laser, which can provide a 200° wide‐field panoramic fundus photo through the utilization of a large elliptical mirror. This innovation, known as ultra‐wide‐field scanning laser ophthalmoscopy (UWF SLO), enables precise characterization of all regions with pathological changes on the retina.…”
Section: The Development Of Fundus Imagingmentioning
confidence: 99%
“…Ultra-widefield scanning laser ophthalmoscopy was developed by combining confocal scanning laser ophthalmoscopy with a concave elliptical mirror. It can record a wider view of the retina of up to 200° in a single image with an acquisition time of less than one second, without the need for pupil dilatation [ 25 , 57 ]. The use of ultra-widefield scanning laser ophthalmoscopy is still limited due to its high cost [ 12 ].…”
Section: Retinal Imaging Modalitiesmentioning
confidence: 99%